2016
DOI: 10.1111/1462-2920.13319
|View full text |Cite
|
Sign up to set email alerts
|

Thiouridine residues in tRNAs are responsible for a synergistic effect of UVA and UVB light in photoinactivation of Escherichia coli

Abstract: Since different wavelengths of light impact different cellular targets, microorganisms exposed to natural sunlight experience a combination of multiple stressors. In order to better understand the effects of sunlight on microorganisms we, therefore, need to understand how different wavelength act alone and in combination. Here, we describe a synergistic effect between UVA and UVB irradiation on viability of Escherichia coli bacteria. To investigate the basis of this synergistic effect we analysed mutant strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 37 publications
1
16
2
Order By: Relevance
“…1 (b)). Sunlight mediated inactivation of non-antibiotic resistant E. coli was also reported in previous studies and was mainly attributed to the DNA damage initiated by UVA and UVB portions of sunlight ( Kadir and Nelson, 2014 ;Probst-Rüd et al, 2017 ).…”
Section: Photo-inactivation Of Ar E Colisupporting
confidence: 71%
“…1 (b)). Sunlight mediated inactivation of non-antibiotic resistant E. coli was also reported in previous studies and was mainly attributed to the DNA damage initiated by UVA and UVB portions of sunlight ( Kadir and Nelson, 2014 ;Probst-Rüd et al, 2017 ).…”
Section: Photo-inactivation Of Ar E Colisupporting
confidence: 71%
“…Previous studies report that UV-B radiation is approximately 100–1000 times more lethal for microorganisms than UV-A [27]. It is well known that the UV-B germicidal effect is mainly based on the direct effect on DNA stability as it overlaps with the DNA absorption region.…”
Section: Discussionmentioning
confidence: 99%
“…UVA is known to be less effective at killing bacteria than UVB or UVC. Probst-Rüd et al (2017) found that UVA radiation mainly induced sublethal effects, such as oxidative stress, protein damage, growth delay and energy metabolism reduction, which could damage cells rather than kill them. In this case, damaged cells can recover and functionalize normally under appropriate conditions, which should be avoided in experiments and applications.…”
Section: Factors Influencing Pdimentioning
confidence: 99%